Research about the reasons why university students practice sport. The example of Granada University - G. Torres; L. Carrasco; J. Medina (Asociación Española de Ciencias del Deporte, 2010)
Through this paper, the motivation of Granada University´s students for the physical activity in the sport program of this organization has tried to be known. With this aim, fifty-five students who are participants in these activities were selected to complete a Lickert´s Scale with six factors and twenty-six items. Next to statistic analysis, the best factor chosen was "Fitness - Health", taking away importance to the aspects related with "Situacional Reasons" and "Self-realization". At the same time, sexual differences related with physical activity in these activities organized by Granada University were determined, verifying that girls value more the socializators and group practice aspects than boys. KEY WORDS: Motivation, physical activity, youngsters, university sports.